Digitalisasi Pengisian Logbook Penggunaan Alat pada Laboratorium Keperawatan - Suardani, Ni Luh Ketut; Ari Kresna Dewi, Ni Luh Gede (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Recording the use of laboratory equipment is done in a logbook or daily log. Logbook is an important document for laboratory managers in managing the improvement of laboratory service quality. The use of logbooks has not been optimal, where recording is still done using conventional methods that are done manually. Filling in the logbook manually causes data on equipment usage to be untraceable, inaccurate and incomplete. Making an application in digital form will facilitate access to equipment data collection. The purpose of this study was to determine the level of feasibility (usability) of filling in the logbook in the form of a QR Code on the use of laboratory equipment in the Nursing Department of Poltekkes Denpasar. The type of research used is quantitative descriptive with a cross-sectional design. The number of samples for the trial of the digital logbook filling application was 60 people. The sampling technique used the stratified random sampling technique. The data collection instrument used the System Usability Scale (SUS) questionnaire. Data analysis was carried out by calculating the average SUS score. The results of the study showed an average score of 71,08, with the level of acceptance of the QR Code application categorized as